Providensia Allah bagi Kebahagiaan Rumah Tangga Kristen - Nurlela Syafrian Oematan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
AbstractThe Christian home is like a vast ocean to be crossed. On the journey across the vast ocean,sometimes you will experience calm, but often it will be turbulent, through typhoons, filled withrocks and icebergs. However, many arks of Christian households are sunk or divorced because ofhitting rocks or complicated problems, and innocent children remain as victims. This happensbecause of the lack of preparation that is carried out before entering the household or also becauseof the lack of preparation that is carried out before entering the household or also because of a lackof vigilance in living a household life, it is necessary to provide God's providence in the household.Therefore, the author uses an inductive method in the form of literary studies as the theologicalbasis for God's providence in marriage for the happiness of Christian households